THE EDUCATIONAL VALUE OF NATIONAL CUSTOMS AND TRADITIONS IN THE ERA OF GLOBALIZATION - Mavlanova Mekhnbonu Obid qizi; Koryogdiyev Zufar Okhunjonovich (Journals Park Publishing, 2023)
The article shows the influence of mass culture on the consciousness and worldview of young people in the modern period of intensive globalization, the upbringing of the younger generation on the basis of national values and traditions.
Keywords: globalization, national tradition, mass culture, transformation of national values, violence, individualism, egocentric ideas.